2000
DOI: 10.1177/002194360003700404
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Process Training on Process and Outcomes in Virtual Groups

Abstract: Virtual groups meet via the Internet every day. When such groups confront large bodies of information in decision making, the group process often becomes confused and chaotic. Process structuration (Giddens, 1979(Giddens, , 1984Poole, Seibold, & McPhee, 1985) provides a theoretical framework by which we can understand group processes and outcomes. This study examines the effects of process structuration by means of a training video on maintenance behavior and outcomes in 55 different student virtual decision-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
3
13
0
Order By: Relevance
“…Additionally, Johnson et al [19] contended that in VLE, the lack of a willingness to participate in teamwork is the most challenging issue that leads to the occurrence of conflicts. Special considerations for effective leadership are required in virtual team collaboration [37,40].…”
Section: The Moderating Effects Of Virtual Leadershipmentioning
confidence: 99%
“…Additionally, Johnson et al [19] contended that in VLE, the lack of a willingness to participate in teamwork is the most challenging issue that leads to the occurrence of conflicts. Special considerations for effective leadership are required in virtual team collaboration [37,40].…”
Section: The Moderating Effects Of Virtual Leadershipmentioning
confidence: 99%
“…Some of the main factors investigated focused on group projects, cultural exchange, and learning quality (Alavi, 1994;Tullar & Kaiser, 2000;Rourke et al, 2001;Belanich et al, 2004;Veermans & Cesareni, 2005).…”
Section: Cmc Research On Collaborative Decision-making and Groupworkmentioning
confidence: 99%
“…Students reported that online peer teams were helpful for achieving higher order learning objectives and students preferred peer teams over instructor-led online discussion. Tullar & Kaiser (2000) investigated the effect of process training in virtual groups, employing a training video on maintenance behavior with student virtual decision-making groups. Results indicated that trained groups had higher levels of social support, greater participation rates, greater satisfaction with their group, wasted less time, and made a significantly Veermans & Cesareni (2005) examined discourse processes in four web-based collaborative learning environments from four countries, Finland, Greece, Italy, and the Netherlands.…”
Section: Cmc Research On Collaborative Decision-making and Groupworkmentioning
confidence: 99%
“…In the process of learning to communicate with their online classroom peers, students have to learn (and create, to some degree) the structure (Tullar & Kaiser, 2000) of what is considered appropriate dialogue within the course. The instructor of the course, in setting the stage for communication by providing discussion questions and guidelines for communication, participates in creating a "cognitive map" (Tullar & Kaiser, 2000, p. 409) for discussion within the course.…”
Section: Literature Reviewmentioning
confidence: 99%